Author Correction: Straightforward preparation of supramolecular Janus nanorods by hydrogen bonding of end-functionalized polymers - Shuaiyuan Han (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.